Status of Vitamin D among Patients Admitted with Acute Exacerbation of COPD in Cox’s Bazar Medical College Hospital (Journal of Medicine, 2022)
Background: Acute exacerbations of COPD (AECOPD) are common and strongly affect disease severity and relative healthcare costs. Vitamin D deficiency is frequent among COPD patients and its role in disease exacerbations is widely debated.Method: This study was carried out in the medicine department of Cox’s Bazar medical college. A total of 50 patients admitted with AECOPD were selected consecutively who had given consent and agreed to carry out 25 (OH) D level assays during the period from January 2021 to December 2021. Inclusion criteria were patients with confirmed cases of COPD. At the enrolment visit, patients were subjected to full clinical history and examination, and pulmonary function testing. Vitamin D [25 hydroxyvitamin D, 25(OH) D] assay was done by Automated Immunoassay Analyzer Model “MINI-VIDAS” using Biomerieux reagent in ELFA (Enzyme linked fluorescence assay) Technology. Vitamin D deficiency was defined as 25(OH) D 30 ng/ ml was recognized as sufficient.Results: Among 50 patients 38 were males and 12 were females. The mean age of patients in this study was 72.2±13.8 years. The mean 25(OH) D level was 22.026±6.0519 ng/ml (95%CI 8.1-40.2). The mean level of vitamin D in males was (22.06±6.08 ng/ml) and in females (21.93±6.24ng/ml) (P= 0.948). Associated comorbidities are present in 54% of patients, among which Hypertension (HTN) contributes in 26%, Diabetes Mellitus (DM) in 18%, coronary artery disease (CAD) in 8%, and cerebrovascular disease (CVD) in 2%. The majority of the participants were former smokers (60%), and the mean pack-year of smoking was 22.09±6.14. In this study, vitamin D levels did not differ among various smoking groups. It was 21.9±8.1 ng/ml in non-smokers, 21.4±5.1 ng/ml in current smokers, and 22.3±6.1 ng/ml in ex-smokers groups (P= 0.904). 56% of the patients belong to low socioeconomic conditions in this study, and 42% were from lower-middle-class families. Most of the patients (86%) were from rural areas, followed by 10% from urban areas and 2% from slum areas. Regarding vocational status, 70% were retired, 10% were housemakers, farmers 6%, and the rest were service holders or business people with mean vitamin D levels of 22.2±5.9 ng/ml, 20.1±8.6 ng/ml, 24.3±2.8 ng/ml and 21.4±6.5 ng/ml respectively. The majority (44%) of patients had mMRC Grade -2 dyspnea, followed by 40% in Grade- 1, 10% in Grade-3, and only 6% of patients had Grade- 4 dyspnea. In the study, only 12% of the patients had sufficient levels of serum vitamin D. The majority had an insufficient level of serum vitamin D (52%) and 36% had a deficient level of serum vitamin D.Conclusion: This study finds a high prevalence of hypovitaminosis D (88%) in AECOPD patients. Vitamin D deficiency and insufficiency are more prevalent in females. In this study, vitamin D levels did not differ between smoking groups.J MEDICINE 2022; 23: 121-125